Networked information and clinical decision making: the experience of Birmingham Heartlands and Solihull National Health Service Trust (Teaching) - Nankivell C; Wallis P; Mynott G (Medical Education, 2001)
Objectives The paper presents the findings of the evaluation of a pilot project to introduce networked information resources into clinical settings in a large NHS Trust and describes the subsequent developments of networked information within the Trust. Design The main purpose of the evaluation was to ascertain whether access to electronic journals and other resources via a networked system offered real benefits to clinical effectiveness. Setting Birmingham Heartlands and Solihull NHS Trust (Teaching). Subjects Medical and administrative staff at Birmingham and Solihull NHS Trust. Results The main conclusions of the evaluation were that: (1) appropriate location of terminals close to clinical areas is vital to ensure that best use is made of networked information resources; (2) rapid access to networked information services saves staff time and allows educational opportunities to be realized; (3) networked information resources enhance rather than replace existing information sources; (4) training and support are essential to maximizing the benefits of networked information services, and (5) such a network can support clinical decision making. Conclusions With the development of clinical governance, the clinical network has assumed even greater importance within the Trust. Timely and easy access to clinical and educational information is crucial to the practice of evidence-based medicine which underpins high quality clinical care. The evaluation led to a number of recommendations which have since been used to develop the clinical network at Birmingham Heartlands and Solihull NHS Trust.